Real-Time Expression Analysis of Selected Anticarsia gemmatalis multiple nucleopolyhedrovirus Gene Promoters during Infection of Permissive, Semipermissive and Nonpermissive Cell Lines - Morgado, Fabricio da Silva (Viruses, 2017)
Baculovirus infection follows a transcriptionally controlled sequence of gene expression that occurs by activation of different viral gene promoter sequences during infection. This sequence of promoter activation may be disrupted by cellular defenses against viral infection, which might interfere with viral progeny formation. In this work, the activity of the ie1, gp64, lef-1, vp39, p6.9 and polh promoters of the Anticarsia gemmatalis multiple nucleopolyhedrovirus was assessed during infection of permissive, semipermissive and nonpermissive cell lines by a novel methodology that detects reporter protein luminescence in real-time. This technique allowed us to characterize in rich detail the AgMNPV promoters in permissive cell lines and revealed differential profiles of expression in cells with limited permissivity that correlate well with limitations in viral DNA replication. Semipermissive and nonpermissive cell lines presented delays and restrictions in late and very late promoter expression. Cells undergoing apoptosis did not inhibit late gene expression; however, viral progeny formation is severely affected. This work demonstrates the application of the real-time luminescence detection methodology and how the promoter expression profile may be used to diagnose cellular permissivity to baculovirus infection.